An analytical ship dynamics study on cruise ship operation and passenger motion sickness assessment - Koh, Priscilla Yi Jing (2015)
This report on An Analytical Ship Dynamics Study on Cruise Ship Operation and Passenger Motion Sickness Assessment presents an overview of the author’s research and findings. Firstly, the background of the simulation software used and the scope of the project are presented. Next, the literature review serves to elucidate previous research efforts, as well as allow readers to better understand seakeeping aspects and motion sickness. Research on the six degree of freedoms, what is motion sickness, the mathematical models for seasickness, wave definitions as well as previous research efforts are presented in the literature review. This report demonstrates the step by step simulation set up comprising details of how the author extracted the cruise vessel hull form from the 2D hull mesher, to how this was inserted into the 3D hull modeller to obtain the compiled hydrodynamic database (CHDB) file. The various settings such as the external conditions, loading condition of the vessel, the voyages that the vessel was set to sail on, the wave scatter configurations as well as the sea state definitions will also be presented. The CHDB configuration that comprises the basic responses that the vessel is set to face, the vessel’s bilge keel as well as the roll damping settings was also elaborated further. Two different voyages were set for the purpose of this project. Initially, only one voyage from Singapore to Hongkong was used. However, in order for comparisons to be made, an additional voyage from Singapore to Phuket was created, with similar settings used. The results from the two voyages are obtained separately. After which, the sea state statistics that comprises the polar diagram as well as the graphical representation of the speed and heading were discussed. The wave scatter diagram statistics were also presented as part of the results. Finally, the results from the two voyages were discussed, with its focus on heave, pitch and roll motions, with respect to motion sickness of passengers on board. The results and findings concluded that passengers on the voyage from Singapore to Hongkong will be more likely to suffer from motion sickness whereas passengers onboard the same vessel from Singapore to Phuket will not be affected from motion sickness effects. Conclusions and recommendations were then made as a wrap up for this project.